교육과정 실행을 위한 커뮤너티 기반 그룹컨설팅에 참여한 유아교사들의 경험 - 박수경(Su-Kyoung Park); 정미라(Mi-Ra Chung) (한국콘텐츠학회 논문지, 17(4), 2017)
Purpose: This research aims at exploring what early childhood teachers experienced in the teachers' community for the national-level curriculum implementation while participating in group consulting. Method: The participants were 10 teachers working at the day care centers located in the capital area. They had joined this study for 9 months, sharing and practicing various strategies related to curriculum implementation through community-based group consulting. Result: First, the teachers came to understand the frame of curriculum from a different point of view. Second, the teachers focused not only on the contents of education but on the methods of education, and shared the forest of feasibility crossing educational plans and the reality. Third, they found various methods to solve the problems and learned transformation ways in the context of curriculum implementation. Fourth, it was verified that nevertheless, there was still complicated and situational dilemma in curriculum implementation. Conclusion: The community-based group consulting was meaningful for the early childhood teachers because it enables them to enhance their professional techniques for the curriculum implementation. 본 연구에서는 국가수준 교육과정 실행을 위한 교사커뮤너티에서 유아교사들이 그룹컨설팅에 참여하면서 어떠한 경험을 하는지 살펴보고자 하였다. 본 연구의 참여자들은 수도권에 소재하고 있는 어린이집 교사 12명이었으며, 10개월 동안 커뮤너티 기반 그룹컨설팅에 참여하면서 교육과정 실행과 관련된 다양한 전략을 서로 나누고 실천하였다. 본 연구의 주요 결과는 다음과 같다. 첫째, 본 연구에서 교사들은 교육과정이라는 틀을 다시 바라보게 되면서 단지 문서상의 교육과정이 아닌 맥락화된 교육과정 실행의 주체자로서 스스로를 다시 생각해 보는 기회를 가졌다. 둘째, 교사들은 교육 계획과 실제를 넘나들면서 실천 가능성의 숲을 서로 공유하였다. 셋째, 그룹컨설팅 과정을 통해 교사들은 문제 해결을 위한 다양한 방법을 모색하면서 교육과정 실행의 맥락에 대한 새로운 지평을 열게 되었다. 넷째, 그럼에도 불구하고 교육과정 실행에 있어 여전히 복잡하고 상황적인 딜레마가 있다는 것을 확인하였다. 본 연구의 결과를 바탕으로 유아교사의 교육과정 실행을 위한 전문성을 향상시킬 수 있는 커뮤너티 기반 그룹컨설팅의 유용성을 논의하였다.